LC-HRMS Analysis of Abelmoschus Manihot Medik from Palu of Central Sulawesi - Rafni Mahyudin Paliwang; Viani Anggi; Rezky Yanuarty; Yasinta Rakanita (Jurnal Penelitian Pendidikan IPA, 2024)
Abelmoschus manihot (L.) Medik is one of the traditional medicinal plants from Palu City, Central of Sulawesi with the Malvaceae plant family and commonly is a traditional medicinal plants recognized fot its therapeutic potential, particularly in antioxidant, anti-inflammatory and wound healing applications. This research aims to identify and characterize the chemical compounds present in Abelmoschus manihot (L.) Medik plant from Palu City, Central of Sulawesi using  liquid chromatography high resolution mass spectrometry (LC-HRMS). This research was collected fresh plant, designed using ethanol extraction from Abelmoschus manihot (L.) Medik and analyzed using mass spectroscopy (LC-HRMS) with Processing Software – MZMine Ver. 3.9.0. The results of this study  provide new insights into the chemical composition of Abelmoschus manihot (L.) Medik and confirm its potential as a source of bioactive compounds that could be futher explored for pharmaceutical development, namely that it contains the main compound Quercetin with a mass of 303.04, Gossypetin; Myricetin with a mass of 319.04, Quercetin 3-O-alpha-L-rhamnoside with a mass of 449.10 Isoquercetin; Hyperoside; Hyperin; Hirsutrin with a mass of 465.10, Gossypol with a mass of 519.20 and rutin with a mass of 291.08.